World economic outlook, october 2015 : adjusting to lower commodity prices - International Monetary Fund (Washintong, D.C. : International Monetary Fund, 2015)
This books reveals that near-term economic growth still looks stronger in advanced economies, compared to the recent past but weaker in the emerging market and developing economies that account for a growing shares of the world output still account for lion's share of the world growth.
Contains World Economic Outlook
mf 25/01/2019
Loans
Keywords: Economic forecasting; Economic conditions; Economic history; Economic development